Char as nanofillers: effects on mechanical performance of char-reinforced polymer composites - Jamal T.; Sapuan S.M.; Siddiqui V.U.; Syamsir A.; Asmawi N.; Harussani M.M. (Elsevier, 2025)
This chapter addresses the use of char, a carbonaceous material produced from the pyrolysis of organic substances, as nanofillers in composite materials and analyzes their significant impact on mechanical performance. Following that, the chapter explores the underlying processes that improve mechanical characteristics in char-reinforced composites, including interfacial interactions, dispersion, and structural compatibility. In addition, the chapter examines prospective applications in areas such as absorbents often utilized as wastewater purification, humidity controllers, and odor absorbers. It also discusses obstacles and future potential, with a focus on sustainable sourcing and environmentally friendly processing techniques. In conclusion, this chapter provides an in-depth examination of char-based nanofillers and their potential to improve the mechanical characteristics of composites, making it a significant resource for academics and practitioners looking for sustainable and high-performance materials. ? 2025 Elsevier Ltd. All rights reserved.